Barriers to the EU Single Services Market - O. V. Biryukova (Vestnik MGIMO-Universiteta)
The EU has the most developed liberalization mechanism in services trade within the framework of an economic bloc. The system of supranational institutions, which decisions are binding upon member states, contributes to a high level of liberalization of trade in services in the EU. However, the creation of a single market for services hasn't completed at all. The reasons are following: not all basic principles for single market are fully applied, and a service is a very specific object for international trade. Financial-economic crisis caused a new wave of protectionism in different countries, which has reflected in the preservation of old and the emergence of new barriers to trade in services within the EU. Integration of services in the Union is accompanied by important trade initiatives at the multilateral level. In the World Trade Organization EU countries negotiate a new agreement on trade in services, and offer provisions which providing transparency, deepening liberalization and investor protection for foreign investors in the market, will also complement and foster the Transatlantic Trade and Investment Partnership (TTIP) EU - USA. Russia is only the fourth among most important partners of the EU in trade in services. At the same time the European Union remains a key Russian partner in trade in services and in goods. There is a considerable potential for growth in this sphere for both partners.